Faktor-faktor yang mempengaruhi kebijakan hutang perusahaan konstruksi, hotel & travel services serta real estate & property yang terdaftar di bursa efek indonesia tahun 2010-2011 - Stephen Lie; Emrinaldi Nur DP; Ruhul Fitrios (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of profitability as measured by ROA (X1), the structure of assets (X2), and dividend policy (X3) on debt or leverage policy (Y). The object of this study is the construction, hotel and travel services as well as real estate & property listed in the Indonesia Stock Exchange in 2010-2011 with a total sample of 60 firms.This study uses secondary data obtained from the Indonesia Stock Exchange. The analytical method used is multiple regression analysis. Data collect from Indonesian Stock Exchange for this industry is thirty company which is collect for 2010-2011.Based on the analysis, it is known that the independent variables that have a significant effect on debt policy (Y) as measured by the DER is the structure of assets (X2). Meanwhile, the profitability (X1), and dividend policy (X3) has no effect on debt policy (Y). The coefficient of determination is 0.355 which shows that 35.5 % of the changes in debt policy is affected by the determinant variables used in the research model while the rest (64.7 %) is explained by other variables.Keywords : Debt Equity Ratio (DER), profitability (ROA), Asset Structure, Dividend Payout Ratio (DPR)